THE EFFECT OF INFOGRAPHIC VIDEO MEDIA IN IMPROVING KNOWLEDGE AND ATTITUDES OF ELEMENTARY SCHOOL STUDENTS IN PALEMBANG CITY ON DIARRHEA PREVENTION - aulia, Estu; Hendawati; Maliha Amin; Faiza Yuniati; Esti Sri Ananingsih (Indonesia Epidemiological Journal, 2025)
Background: Diarrhea is one of the health problems that frequently occurs among elementary school children and can lead to serious consequences if not properly addressed. Preventive efforts through health education are essential, one of which is utilizing engaging and easily understandable learning media for children. Objective: This study aims to determine the effect of animated infographic video media on improving the knowledge and attitudes of third-grade students at SDN 118 Palembang in diarrhea prevention. Methods: The research design used was a quasi-experimental design with a one-group pretest-posttest approach. The study sample consisted of 59 students selected using a total sampling technique. The instruments used were knowledge and attitude questionnaires that had been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The study showed an increase in knowledge scores, with the mean pretest score rising from 12.54 to 18.14 in the posttest, as well as an increase in attitude scores from a mean of 44.88 to 48.61. Conclusion: Statistical tests showed a significant difference between the scores before and after the intervention, both in knowledge (p = 0.000) and attitude (p = 0.000). These findings demonstrate that animated infographic video media has a positive effect on improving students' knowledge and attitudes regarding diarrhea prevention. Recommendation: This media can be used as an effective and engaging educational strategy to support health promotion programs in elementary schools.